Tanggung Jawab Notaris Terhadap Perjanjian Pengikatan Jual Beli Saham Akibat Peralihan Saham Tanpa Rapat Umum Pemegang Saham - Weni Mariati; Maryano M.; Nurwidiatmo N (Postgraduate of Jayabaya University, 2018)
Each shareholder can indicate his concerns through the General Meeting of Shareholders, as the highest forum in a limited liability company which is having undivided power. Shareholders will have voting rights proportional to the amount of capital (shares) invested, then sale and purchase of shares transaction must comply with the provisions of articles of association of a limited liability company, and the applicable laws specifically regulated regarding sale and purchase of shares agreements. In the Decision Number 259/Pdt.G/2017/PN.Jkt.Sel, has been stated the transfer of shares without the through the General Meeting of Shareholders. The method used in this study is a normative and empirical juridical research method. Data analysis has been using a qualitative juridical analysis. As the results of the study, it can be stated that the actions taken by one of the company's shareholder, specifically by making a transfer of shares without the Annual General Meeting of Shareholders and without an Extraordinary General Meeting of Shareholders is allowed, because of the rules regarding the use of Circular Resolution of Shareholders. A Notary has the authority and is given responsibility to assist the community in order to make a proper agreement in accordance with the applicable laws and regulations, so that the Notary can warrant the legal standing for the parties involved in making the agreement